2017
DOI: 10.4171/prims/53-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Alexander Polynomials of Hyperbolic Links

Abstract: In this paper we apply the twisted Alexander polynomial to study the fibering and genus detecting problems for oriented links. In particular we generalize a conjecture of Dunfield, Friedl and Jackson on the torsion polynomial of hyperbolic knots to hyperbolic links, and confirm it for an infinite family of hyperbolic 2-bridge links. Moreover we consider a similar problem for parabolic representations of 2-bridge link groups.2010 Mathematics Subject Classification. Primary 57M27, Secondary 57M05, 57M25. 1 2 TAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Then ρ 75 ε • φ is conjugate to ρ K a for some a and ε ∈ {±1}. However, looking back to (23), we see that ∆ 75,ρ 7 5 ±1 ∆ K,ρ K a . Thus, while the ordinary Alexander polynomial does not detect K 7 5 , TAP does.…”
Section: Montesinos Tangle and Montesinos Linkmentioning
confidence: 90%
“…Then ρ 75 ε • φ is conjugate to ρ K a for some a and ε ∈ {±1}. However, looking back to (23), we see that ∆ 75,ρ 7 5 ±1 ∆ K,ρ K a . Thus, while the ordinary Alexander polynomial does not detect K 7 5 , TAP does.…”
Section: Montesinos Tangle and Montesinos Linkmentioning
confidence: 90%
“…Furthermore, K is fibered if and only if the leading coefficient of T K is equal to 1. Morifuji and Tran [Mori12,MoTr14,MoTr17] showed that Conjecture 9.3 holds for a certain class of 2-bridge knots. Later, Agol and Dunfield [AD20] showed that equality in Conjecture 9.3 holds for all libroid hyperbolic knots in S 3 , including all 2-bridge knots.…”
Section: Conjectures and Questionsmentioning
confidence: 99%
“…The class of libroid knots is closed under Murasugi sum and contains all special arborescent knots obtained from plumbing oriented bands. See [MoTr17] for a generalization of Conjecture 9.3 for links. 9.4.…”
Section: Conjectures and Questionsmentioning
confidence: 99%
“…The hyperbolic torsion conjecture proposed in [5] states that for a hyperbolic knot K, the TAP associated to a lift ρ 0 of the holonomy representation detects the genus and fibredness of K. It was generalized to hyperbolic links in [9]. According to [9] Remark 3.4, the conjecture for a m-component alternating link L is just the same as deg ∆ ρ0 L = 4g(L) + 2(m − 2). It is known that the Borromean link is fibred with genus 1.…”
mentioning
confidence: 99%